Presensi Kurikulum Takmiliyah Pesantren dalam Prespektif Pendidikan - Wahyudi Hidayah (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study was to determine the presence of the walisongo pesantren takmiliyah curriculum. This type of research was qualitative with analytical methods. As a native Indonesian Islamic educational institution, Islamic boarding schools have shown success in maintaining their existence even since the pre-independence era, especially related to the world of education. The existence of MDT is very influential among Islamic boarding schools by the way the subjects are determined and the program structure is structured, the next step is to develop a program for each subject and the development of this program is directly prepared by the madrasa or a group of madrasas. As an Islamic educational institution, pesantren has elements of kyai, santri, huts, mosques, learning methods and the yellow book.One of the most familiar curricula which is equivalent to formal education is Madrasah Diniah Takmiliah (MDT) which is the best solution in overcoming the shortage of religious learning in formal education. Its existence has also been recognized by law number 3201 of 2013 concerning the standard of services for diniah takmiliyah and the government has dominated policies towards pesantren where pesantren policies are approved and implemented by the government and madrasas. In the National education system, Madrasah Diniyah Takmiliyah Awaliyah have a clear position and even their existence has been stated in Law No. 20 of 2003 concerning the National Education System.